2017
DOI: 10.1016/j.neuron.2017.06.048
|View full text |Cite
|
Sign up to set email alerts
|

A Requirement for Mena, an Actin Regulator, in Local mRNA Translation in Developing Neurons

Abstract: Summary During neuronal development, local mRNA translation is required for axon guidance and synaptogenesis, and dysregulation of this process contributes to multiple neurodevelopmental and cognitive disorders. However, regulation of local protein synthesis in developing axons remains poorly understood. Here, we uncover a novel role for the actin-regulatory protein Mena in the formation of a ribonucleoprotein complex that involves the RNA-binding proteins HnrnpK, and PCBP1, and regulates local translation of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
37
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(40 citation statements)
references
References 90 publications
3
37
0
Order By: Relevance
“…Next, to capture the targets of CELF6 in vivo, we chose a region approximately 60-200 nucleotides in size (80-150 kDa) to purify from lysates of 4 pools of CELF6-YFP/HA+ brains. Similar to Vidaki et al's study of Mena (25), we found that the stringent lysis and wash conditions of standard CLIP protocols were incompatible with CELF6 IP (not shown). Therefore, to enable rigorous statistical definitions of CLIP targets, we also collected 4 replicates of CLIP samples generated from pools of 3-4 brains from 4 independent litters, and a key additional control:.…”
Section: Celf6 Primarily Associates With 3'utrs Of Target Mrnas In Vivosupporting
confidence: 88%
“…Next, to capture the targets of CELF6 in vivo, we chose a region approximately 60-200 nucleotides in size (80-150 kDa) to purify from lysates of 4 pools of CELF6-YFP/HA+ brains. Similar to Vidaki et al's study of Mena (25), we found that the stringent lysis and wash conditions of standard CLIP protocols were incompatible with CELF6 IP (not shown). Therefore, to enable rigorous statistical definitions of CLIP targets, we also collected 4 replicates of CLIP samples generated from pools of 3-4 brains from 4 independent litters, and a key additional control:.…”
Section: Celf6 Primarily Associates With 3'utrs Of Target Mrnas In Vivosupporting
confidence: 88%
“…CYFIP2 has homology with the translation repressors, the eIF4E binding proteins (eIF4E-BPs) ( Napoli et al., 2008 ), and can potentially help to silence mRNA translation as the RNP is trafficked along the axon. Interestingly, like CYFIP, Mena has recently been shown to have a dual function in regulating both actin polymerization and mRNA translation ( Vidaki et al., 2017 ). Mena, but not its paralogs VASP and EVL, associates with a specific set of mRNAs and is a key regulator of Dyrk1a synthesis in axons in response to BDNF stimulation ( Vidaki et al., 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…The findings show clearly that hMENA 11a transfection in cells that do not contain this isoform inhibits different ECM proteins. In view of the recent published results on the novel role for Mena in the regulation of local translation of specific mRNAs in developing axons, including FN1 mRNA, it could be posited that hMENA 11a restrains the posttranscriptional effect of hMENA [ 55 ]. Our data show that hMENA 11a inhibits the secretion of β1 integrin ligand collagens, laminin, and fibronectin (Fig.…”
Section: Discussionmentioning
confidence: 99%